Case Report: Pregnancy with Systemic Lupus Erythematosus (SLE) - Ika Hermawati; Fitriana Murriya Ekawati (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2019)
A 24-year-old female patient who was pregnant with a gestational age of 30 weeks came to attend an integrated prenatal check-up at Daren Village Hall at the invitation of the village midwife on April 14, 2017. During the examination, there were no complaints except a lack of appetite. The patient comes by the husband, but the husband cannot accompany him during the examination process because he will work. The patient has been married for 2 years, where the pregnancy at the time of this examination is the first pregnancy.